Teungku Dayah dan Kekuasaan Panoptik (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Abstract: This study examines the teungku dayah and panoptic power. It explores two   main questions that firstly what serves as the basic for the Acehnese society obedience towards the teungku dayah? What power model that the tengku dayah apply so the people  total obedience is honestly expressed whether in front and behind them. Theoretically,  this study refers to power relation and hermeneutic theory that are introduced by Michel  Foucault. The data of this study are collected through observation, in-depth interview and  text studies. By closely study some dayahs (traditional Islamic boarding school) in north  Aceh district, this study finds that teungku dayah could be determinant figure in  Acehnese society. It is because not only they are religiously knowledgeable persons that  are justified by religious norms, it is also influenced by three other resources: sacred  (keuramat), blessed (beureukat) and accursed (temeureuka). As the sacred figure,  Acehnese believe that teungku dayah could mediate God’s blessings to them. Against or  defy to them could cause accurses. The belief of being accursed if one is defiant toward  the Tengku, grants the total obedience toward the Tengku. These three concepts are  crafted in people minds, hearts, and emotion so as if they are always being watched by  the teungku any time and any place. Perhaps Cross Circuit Television (CCTV) best  represents this condition in latest surveillance technology. Thus, these sources grant  teungku dayah the panoptical power that is nonviolent, persuasive, absent, remote, total  and comprehensive.Abstrak: Studi ini mengkaji tentang teungku dayah dan kekuasaan panoptik. Pertanyaan  utama yang dikupas adalah apa yang mendasari lahirnya kepatuhan total masyarakat  Aceh terhadap teungku dayah dan model kekuasaan seperti apa yang dimiliki oleh  teungku dayah sehingga kepatuhan masyarakat terhadap mereka tidak hanya berlaku di  depan tetapi juga di belakang. Proses kajian dilakukan dengan menggunakan perspektif  teoritik kekuasaan Michele Faucault dan metode hermenutik. Maka pelbagai data yang  digali melalui observasi, wawancara mendalam dan studi dokumen diperlakukan sebagai  teks sosial. Lalu, pelbagai data tersebut ditafsirkan melalui teknik tafsir lingkaran  hermeneutik. Penelitian yang dilakukan di beberapa dayah di Aceh Utara ini menemukan  bahwa kekuasaan teungku dayah terhadap masyarakat Aceh selain didasari oleh  penguasaan ilmu agama dan justifikasi normatifitas agama juga dipengaruhi oleh 3 (tiga)  sumberdaya lainnya yaitu keuramat (karamah), beureukat(barakah) dan temeureuka (kualat).. Maka kekuasaan teungku dayah terhadap masyarakat Aceh bersifat panoptik  yaitu tanpa kekerasan fisik, tanpa paksaan, tanpa kehadiran, jarak jauh, total dan  menyeluruh.
Keywords: Teungku dayah; Aceh; kekuasaan panoptik